The Effect Of Localized Circumferential Residual Stress On Pressurized Stress State Of CT Reconstructed Vessels: A Finite Element Study - Vittorio Lissoni; Martina Schembri; Giulia Luraghi; Alessandro Caimi; Virginia Fregona; Mauro Di Giancamillo; Jessica Bassi; Ferdinando Auricchio; Michele Conti; Gabriele Dubini; Francesco Migliavacca; Jose Felix Rodriguez Matas (Annals of Biomedical Engineering, 2026)
Purpose Residual stresses are intrinsic stresses present in arteries even in the absence of external loads or blood pressure. They originate during growth and remodeling and contribute to vascular mechanical equilibrium. Despite advances in computational methods, incorporating residual stresses into patient-specific vascular models remains challenging. Evidence regarding the influence of circumferential residual stresses on physiological loading in realistic anatomies is still limited. Methods We combined in vitro imaging, mechanical testing, and finite element (FE) simulations to incorporate residual stresses into a pressurized porcine aorta model. Medical images were acquired in both pressurized and zero-stress states, the latter obtained after 2 h of longitudinal cutting. Locally measured mechanical properties from distinct aortic regions were used to define an orthotropic hyperelastic material response. Residual stresses were restored by simulating vessel closure under displacement-controlled boundary conditions with a tied contact interface. Stress distributions were then compared in FE pressurization simulations performed with and without residual stresses. Results Residual stresses substantially influenced the predicted stress fields. They homogenized stress across the vessel thickness and reduced stress concentrations near the lumen. Moreover, lumen cross-sectional areas at 120 mmHg aligned more closely with experimental measurements when residual stresses were included. In contrast, neglecting residual stresses produced an average overestimation of lumen area by 4.84% and stress peaks up to 50% higher in the inner wall. Conclusion This study highlights the importance of accounting for residual stresses in biomechanical vascular simulations. Incorporating them improves prediction accuracy and reduces artificial stress concentrations, which is crucial for patient-specific risk assessment and surgical planning.

Angiostrongylus vasorum in a Red Panda (Ailurus fulgens): Clinical Diagnostic Trial and Treatment Protocol - Mara Bagardi; Vanessa Rabbogliatti; Jessica Bassi; Daniela Gioeni; Maurizio Oltolina; Luca Villa (Acta Parasitologica, 2021)